Certain types of functions via βθ-open sets - Caldas, Miguel (Sarajevo Journal of Mathematics, 2017)
New classes of functions, called somewhat βθ-continuous, somewhat βθ-open and hardly βθ-open functions, has been defined and studied by making use of βθ-open sets. Characterizations and properties of these functions are presented.